Pengaruh Kebijakan Restrukturisasi Pembiayaan dan Tingkat Efisiensi Terhadap Stabilitas Sistem Keuangan Bank Syariah Di Indonesia dengan Ukuran Perusahaan Sebagai Variabel Kontrol (Study Kasus Pada Saat Pandemi Covid 19 Tahun 2019-2021) - Putri, Amila Zamzabila (Program Studi Magister Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Sunan Kalijaga, 2023)
The financial system in a country is a very important sector, so it is very important to keep the financial system stable. The financial system's stability can measure bank resilience in dealing with the impact of the financial crisis. The phenomenon of the crisis that is being experienced by Indonesia is a crisis due to the pandemic Covid 19 which has an effect on economic health around the world. For this reason, in this study, they want to know the effect of restructuring policies and the level of bank efficiency on the financial stability of Islamic banks. Quantitative research with secondary data from the results of the financial statements of each bank used in this study. PanelData Regression Method Using 6 Islamic Banks used as a research sample with a time period from Q1 in 2019 to Q4 in 2021. The results of the study show that the restructuring policy and company size have a significant positive effect on the financial stability of Islamic banks, while the variables of the level of efficiency projected have no effect on the financial stability of Islamic banks.